When the paediatric intensive care unit becomes home: A hermeneutic‐phenomenological study. Issue 3 (4th December 2019) - Frechette, Julie; Lavoie‐Tremblay, Mélanie; Kilpatrick, Kelley; Bitzas, Vasiliki
Abstract: Background: Family‐centred care is the dominant model for providing nursing care in paediatrics. Unit layout has been shown to impact nurses' ability to provide family‐centred care. Little is known about the meanings and experiences of paediatric intensive care unit nurses concerning the care they provide to families within their unique physical setting. Aim: This study examined paediatric intensive care unit nurses' lived experience of caring for families following a major hospital transformation project, which included the construction of a new unit and quality improvement changes. Study design: A hermeneutic‐phenomenological design was selected to study a paediatric intensive care unit in a large Canadian paediatric teaching hospital. Methods: Data were collected over a 6‐month period through individual interviews, photographs, participant observation, and document review. The sample consisted of 15 paediatric intensive care unit nurses who experienced the unit both pre‐ and post‐transformation. Data were analysed in an ongoing fashion using the method described by Benner to identify common and divergent meanings. Results: Despite pride in offering a family‐friendly environment, nurses' practice prejudiced a family focus in favour of patient‐centred care. Nurses in this study negotiated physical and practice spaces with families by interpreting that nurses do not belong in the home‐like patient room and exhibiting gatekeeping comportments. Conclusion: Although similar nurse comportments have been identified in prior works, no previous studies have identified these as forming a pattern of negotiating spaces with families. Relevance to clinical practice: This study provides insights into the lived experience of paediatric intensive care unit nurses in relation to family care, which can stimulate reflections at an organizational level about creating environments where nurses and families can both feel at home.